Enzymatic initiation of DNA synthesis by yeast DNA polymerases. - Plevani, P (1977)
Partially purified yeast RNA polymerases (RNA nucleotidyltransferases) initiate DNA synthesis by yeast DNA polymerase (DNA nucleotidyltransferase) I and to a lesser extent yeast DNA polymerase II in the replication of single-stranded DNA. The enzymatic initiation of DNA synthesis on phage fd DNA template occurs with dNTPs alone and is further stimulated by the presence of rNTPs in DNA polymerase I reactions. The presence of rNTPs has no effect on the RNA polymerase initiation of the DNA polymerase II reaction. RNA polymerases I and III are more efficient in initiation of DNA synthesis than RNA polymerase II. Analyses of the products of fd DNA replication show noncovalent linkage between the newly synthesized DNA and the template DNA, and covalent linkage between the newly synthesized RNA and DNA.